2021
DOI: 10.1093/dote/doab052.632
|View full text |Cite
|
Sign up to set email alerts
|

632 Sutured Versus Mesh-Augmented Hiatus Hernia Repair: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Repair of large hiatus hernias is increasingly being performed. However, there is no consensus for the optimal technique for hiatal closure between sutured versus mesh-augmented (absorbable or non-absorbable) repair. This meta-analysis systematically reviewed published randomized control trials (RCTs) comparing sutured versus mesh-augmented hiatus hernia (HH) repair. Our primary endpoint was HH recurrence at short- and long-term follow-up. Secondary endpoints were: surgical complications, operative times, dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Petric et al 27 also made an effort to pool the analyses of current RCTs and studies with longer term outcomes. They pooled the results of 7 RCTs comparing suture versus mesh augmented repairs of the hiatal hernia.…”
Section: Long Term Outcomesmentioning
confidence: 99%
“…Petric et al 27 also made an effort to pool the analyses of current RCTs and studies with longer term outcomes. They pooled the results of 7 RCTs comparing suture versus mesh augmented repairs of the hiatal hernia.…”
Section: Long Term Outcomesmentioning
confidence: 99%
“…In 2022, Petric J. et al [104] analyzed seven randomized controlled trials (RCTs) comparing mesh cruroplasty of the EH (non-absorbable mesh: n = 296; absorbable mesh: n = 92) with suture crurorrhaphy (n = 347). The authors found no significant differences between the groups regarding short-term hernia recurrence (within 6 -12 months): 10.1 % with mesh versus 15.5 % with suture crurorrhaphy, p = 0.22; and long-term hernia recurrence: within 3 -5 years, 30.7 % with mesh versus 31.3 % with suture crurorrhaphy, p = 0.69.…”
Section: T a Tarasov L Y Markulanmentioning
confidence: 99%
“…The only statistically significant difference was that mesh placement required a longer operating time. The authors of the meta-analysis concluded that both methods provided good and comparable clinical results, with the suture-only method still being the relevant approach [104].…”
Section: T a Tarasov L Y Markulanmentioning
confidence: 99%
“…This study confirms the results of many other studies that have shown that a cruroplasty with sutures is as effective as a cruroplasty reinforced by either absorbable or nonabsorbable mesh. [3][4][5] Some aspects of this article deserve comments. Most of the studies mentioned in the discussion evaluated the use of mesh for the repair of large paraesophageal hernias, a different disease and a more complex operation, [3][4][5][6] whereas in this study, only patients mostly with small sliding hernias were included.…”
mentioning
confidence: 99%